2002
DOI: 10.1074/jbc.m112472200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Endocytosis of Activin Type II Receptors by a Novel PDZ Protein through Ral/Ral-binding Protein 1-dependent Pathway

Abstract: Using yeast two-hybrid screening, we have identified a mouse Postsynaptic density 95/Discs large/Zona occludens-1 (PDZ) protein that interacts with activin type II receptors (ActRIIs). We named the protein activin receptor-interacting protein 2 (ARIP2). ARIP2 was found to have one PDZ domain in the NH 2 -terminal region and interact specifically with ActRIIs among the receptors for the transforming growth factor ␤ family by the PDZ domain. Interestingly, overexpression of ARIP2 enhances endocytosis of ActRIIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
1
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 58 publications
0
89
1
6
Order By: Relevance
“…Internalization of the type II activin receptor (ActRII) was shown to be promoted by activin receptor-interacting protein 2 (ARIP2) [113]. Overexpression of ARIP2 attenuated the activin-induced reporter expression, indicating that internalization of ActRII negatively regulates activin signaling.…”
Section: Arip2mentioning
confidence: 99%
“…Internalization of the type II activin receptor (ActRII) was shown to be promoted by activin receptor-interacting protein 2 (ARIP2) [113]. Overexpression of ARIP2 attenuated the activin-induced reporter expression, indicating that internalization of ActRII negatively regulates activin signaling.…”
Section: Arip2mentioning
confidence: 99%
“…However, ARIP1 mainly distributed in nerve tissues, ARIP2 widely existed in tissues. The high expression of ARIP2 mRNA could be detected in liver tissue by Northern blot [7] . In order to investigate the kinetic changes of ARIP2 expression, we used activin A and endotoxin LPS to stimulate Hepal-6 cells, and then examined the expression of ARIP2 mRNA.…”
Section: Discussionmentioning
confidence: 90%
“…ARIPs have obvious expression and distribution diversity, which are key factors to the histological specificity of activin action [6][7][8] . It has been demonstrated that both ARIP1 and ARIP2 are inhibitors of activin signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations